THE INFLUENCE OF MOTIVATION TO WARD THE EMPLOYEES WORK PERFORMANCE IN IT CENTER MANADO - Stephanus Stephanus (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of research is to know the motivational influence toward the work performance of the workers in IT center Manado. The method used is the surveys methodology by using a questionnaire as a means of data gatherers , to define the onnection between variables research through the testing of hypotheses Research variable is as free variable, the influence of motivation as (X) variable and the performance of the employee as limited variable (Y). The sample gathering techniques using the Slovin formulas, with the number of 30 respondents, using likert scale, and simple regression analysis. The result the regression analysis shows the value of the influence of Motivation (X) toward the performance of the employee (Y) in IT Center, Manado as the test result of the correlation obtained r-hitung = 0,150 < r-tabelnya = 0,317 juga F-hitung 0,647 < F-tabel 4,196 dan t-hitung 0,805 < t-tabel 1,701 (r-count = 0,150 < r-table = 0,317 also f-count 0,647 < F-table 4,196 and t-count 0,805 < t-table 1,701) which means its influence is very small . The influence of motivation to work performance of the employees in IT Center Manado is probably influenced by other factors. This reflected on the results of correlation determinant only 2.3 % and the rest influenced by other factors which aren’t researched.